Perancangan Sistem Informasi Pembelian dan Penjualan Berbasis Web Pada Toko Sumber Jaya - Hansen, Hansen; Saputra, Chindra; Sandra, Dodi (LPPM STIKOM Dinamika Bangsa, 2024)
Sumber Jaya store is a business that moves in selling foods such rice, cigarette, sugar, bread, egg, beverages, shrimp crisp and other. The food business is situated in Singkut, specifically on Jalan Budi Utomo, Benteng River. The current method of data processing for procurement of products relies on physical books or hard copy documents, leading to many issues such as data errors, including mistakes in recording product names, product prices, and improper management of product supply. Hence, the objective of this study is to address this issue by creating a sales information system that employs the PHP programming language and MYSQL database. The author employs the waterfall process to construct a sales information system and using UML (Unified Model Language) to generate a range of diagrams, including use case diagrams, activity diagrams, and class diagrams. The recently built system generates structured output that encompasses item data, purchase data, and sales data. Additionally, it offers crucial reports that enable Sumber Jaya shops to efficiently and precisely collect information